2020
DOI: 10.1108/lodj-01-2020-0026
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ethical leadership on employee creative deviance: the mediating role of job autonomy

Abstract: PurposeThis study aims to explore the impact of ethical leadership on employee creative deviance, with job autonomy as a mediator and creative self-efficacy as a moderator between job autonomy and creative deviance.Design/methodology/approachA survey was developed based on construct measures from the literature. A total of 316 responses were received from employees of information and communication technology companies located in China's Pearl River Delta.FindingsBoth ethical leadership and job autonomy have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 64 publications
(122 reference statements)
4
51
0
Order By: Relevance
“…The myth between temporal leadership and job autonomy. Autonomy in the workplace can be promoted by leadership styles [13,66]. For instance, ethical leaders provide employees with greater autonomy at work by providing social cues embedded in values, work requirements, and expectations [13].…”
Section: 33mentioning
confidence: 99%
See 3 more Smart Citations
“…The myth between temporal leadership and job autonomy. Autonomy in the workplace can be promoted by leadership styles [13,66]. For instance, ethical leaders provide employees with greater autonomy at work by providing social cues embedded in values, work requirements, and expectations [13].…”
Section: 33mentioning
confidence: 99%
“…Autonomy in the workplace can be promoted by leadership styles [13,66]. For instance, ethical leaders provide employees with greater autonomy at work by providing social cues embedded in values, work requirements, and expectations [13]. Some studies [67] found that job autonomy fully mediates the effect of transformational leadership on work engagement.…”
Section: 33mentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the present analysis considers job autonomy as the mediating variable to explain the relationship between CSR and employee creativity. In this context, the mediating role of job autonomy to explain employee creativity is already established in the literature [11,18]. However, its potential effect from the viewpoint of CSR has not been given due consideration.…”
Section: Introductionmentioning
confidence: 99%